2019
DOI: 10.1001/jamaophthalmol.2018.5243
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of 5 Validated Symptom Questionnaires as Screening Instruments for Dry Eye Disease

Abstract: Dry eye disease is a complex heterogeneous and multifactorial condition. 1 Validated questionnaires are frequently used to screen for dry eye symptoms before assessing tear film homeostasis markers. 1 Recently, the international Tear Film and Ocular Surface Society Dry Eye Workshop II (TFOS DEWS II) recommended the use of the Ocular Surface Disease Index (OSDI) and 5-item Dry Eye Questionnaire (DEQ-5) as part of the dry eye diagnostic criteria. 1 This prospective, investigatormasked, diagnostic accuracy study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 7 publications
1
15
1
Order By: Relevance
“…This falls into the criteria for a good and useful diagnostic test [30,31]. Contrary to findings from the current study, Wang et al [32] reported DEQ-5 to not have a good discriminative ability A notable difference between the current study and that of Wang et al is the study population. The current study sampled Africans while Wang et al sampled Europeans, South and East Asians.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This falls into the criteria for a good and useful diagnostic test [30,31]. Contrary to findings from the current study, Wang et al [32] reported DEQ-5 to not have a good discriminative ability A notable difference between the current study and that of Wang et al is the study population. The current study sampled Africans while Wang et al sampled Europeans, South and East Asians.…”
Section: Discussioncontrasting
confidence: 99%
“…The same formula was used to calculate subsection (ocular symptoms, visual related function, and environmental triggers) scores. Overall OSDI score was grouped as normal (<13), mild (13)(14)(15)(16)(17)(18)(19)(20)(21)(22), moderate (23)(24)(25)(26)(27)(28)(29)(30)(31)(32) and severe (>32) [23]. An individual with OSDI score ≥13 was considered positively symptomatic for diagnosis of dry eye disease [23].…”
Section: Questionnairesmentioning
confidence: 99%
“…Ocular comfort was assessed using the OSDI, DEQ-5, and the Symptom Assessment in Dry Eye (SANDE) questionnaires during the treatment period. [15] The overall SANDE score was calculated as the geometric mean of the frequency and severity scores. [16] Participants were advised to contact the study investigators during the study period to report adverse events at any time.…”
Section: Measurementsmentioning
confidence: 99%
“…A 2015 study demonstrated that SANDE had significant correlation and negligible score differences to OSDI implying its potential to provide shorter, quicker, and comparably reliable measures of dry eye symptoms to that of OSDI [30]. Recent 2019 studies found that both OSDI and SANDE have superior discriminative ability in detecting dry eye signs compared to other questionnaires including SPEED [31]. SANDE has also been utilized to assess the efficacy of certain dry eye treatments including the new TearCare system [32].…”
Section: Symptom Assessment Questionnaire In Dry Eye (Sande)mentioning
confidence: 99%